2006
DOI: 10.1007/s10067-006-0357-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolated renal sarcoidosis: a rare presentation of a rare disease treated with infliximab

Abstract: Sarcoidosis is a multisystem disease characterized by noncaseating granulomatous reaction frequently involving the lymph nodes, lungs, liver, skin, and eyes. Acute renal failure (ARF) as an isolated manifestation of sarcoidosis is rare. We describe a case of sarcoidosis presenting as transient polyarthritis and ARF due to isolated granulomatous infiltration of the renal parenchyma. Renal biopsy showed granulomatous interstitial nephritis with noncaseating granulomas consistent with sarcoidosis. Bacterial, fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…[34] Infliximab may be effective in relapsing or steroid-resistant patients. [35] in very carefully selected cases, renal transplantation may be appropriate. Sarcoidosis may appear in the allografted organ.…”
Section: Specific Organ Involvement and Clinical Manifestationsmentioning
confidence: 99%
“…[34] Infliximab may be effective in relapsing or steroid-resistant patients. [35] in very carefully selected cases, renal transplantation may be appropriate. Sarcoidosis may appear in the allografted organ.…”
Section: Specific Organ Involvement and Clinical Manifestationsmentioning
confidence: 99%
“…Furthermore, infliximab has been used with success to treat renal sarcoid. 35 Another approach would have been to rechallenge our patient with adalimumab, as reported by others, 36 or switch treatment to etanercept, which is a fusion protein of soluble TNF receptor and human IgG. However, there is evidence that etanercept is not effective in the treatment of sarcoidosis.…”
Section: Discussionmentioning
confidence: 96%
“…Although there have been no comparative trials between the biologic agents for sarcoidosis, infliximab is the most heavily reported medication in the literature [611], and overall has shown great promise in the treatment of sarcoidosis patients refractory to more conventional therapies [6, 7, 12, 26]. Favorable outcomes of infliximab therapy in patients who have renal sarcoidosis [13], vertebral sarcoidosis [14], joint sarcoidosis [15], optic neuropathy [16], pulmonary sarcoidosis [6, 17], retinal vasculitis [18], cutaneous sarcoidosis [35, 22], neurosarcoidosis [19], and cardiac sarcoidosis [20] have also been reported.…”
Section: Discussionmentioning
confidence: 99%